The European Parliament's involvement in the EU response to the corona pandemic: A spectator in times of crisis - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2020)
Since the beginning of 2020, European Union (EU) institutions have adopted a number of measures in response to the corona pandemic to coordinate Member States' containment efforts and provide European resources for joint reconstruction. The EU recovery fund will set the course that will shape European integration. Nevertheless, despite its budgetary rights, the European Parliament (EP) has remained an onlooker for most of these decisions, as it did during the euro and refugee crises. In order to strengthen democratic legitimacy and the European perspective, the EP should be more closely involved in the EU recovery fund in the short term, and in the long term be given a co-decision role in the EU's crisis policy instruments.
Keywords: 320